BALB/c Mouse Is a Potential Animal Model System for Studying Acute and Chronic Genotype 4 Hepatitis E Virus Infection - Li, Yunlong; Long, Feiyan; Yang, Chenchen; Hao, Xianhui; Wu, Jian; Situ, Jianwen; Chen, Shuangfeng; Qian, Zhongyao; Huang, Fen; Yu, Wenhai (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) is the main pathogen of hepatitis worldwide. However, its infection biology and pathogenesis remain largely unknown. Suitable small animal models are required to advance the study of HEV infection. Although an efficient model of genotype 1 (gt1) and gt3 HEV infection has been established in human liver chimeric mice, the infectivity of gt4 HEV infection in mice has not been comprehensively characterized. In this study, immunocompromised BALB/c nude, immunocompetent BALB/c, and C57BL/6 mice were inoculated with either gt3 or gt4 HEV (19 HEV strains, including human, swine, macaque-adapted, and cow HEV strains). Infectivity was identified by viral RNA and antigen detection, inflammation, and histopathological analysis. Then, HEV-infected BALB/c mice were treated with antiviral drugs. Acute HEV infection was established in BALB/c mice inoculated with eight gt4 HEV strains. However, gt3 HEV strains failed to achieve active HEV infection. HEV infection was established in BALB/c nude and regular mice inoculated with gt4 HEV but not in C57BL/6 mice. Gt4 HEV infection resulted in rapid viremia and high titers in feces, sera, and replication sites. HEV infection in mice showed no gender preference. Furthermore, chronic gt4 HEV infection was well imitated in BALB/c mice for 32 weeks and caused liver fibrosis. Conclusions: BALB/c mice have a great potential for reproducing the process of gt4 HEV infection. The successful establishment of a gt4 HEV small-animal model provides an opportunity to further understand HEV infection biology and zoonotic transmission and develop anti-HEV vaccine.